Applied Internet of Things(IOT) In Temperature and Vibration Monitoring System for Milling Machine - Mohd Said, Nurul Hani Afiqah; Yusof, Yusri (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Tool Condition Monitoring in the machine industry is vital for the preventive maintenance of the cutting tool, leading to technology improvement in Industrial Revolution 4.0. Especially in Small and Medium-sized Enterprise, it is challenging to implement monitoring system into their machine due to the high cost of development and expert handling the system. The need to have a well-developed system that is low cost and dependable for them to utilise in the shop floor becomes the key for this research. Two reliable sensors were tested: thermocouple to measure the temperature data and accelerometer, ADXL335 to measure the vibration data during the end milling machining process. The relationship between these two sensors, together with the tool life, was recorded and observed. The research also proposed implementing Internet of Thing in monitoring system for milling machine to help the working personnel monitor the machine tool condition in any location if it shared the same local network. The system also operated and display real-time data through an online platform called Blynk. Through the mobile application, the user can monitor the sensors’ data and be notified if there is unstable behaviour during the cutting process via smart device. The alert notification will be popped up in the smart device along with the alarm so that the person in charge of the machining can alert and take further actions. Moreover, the effectiveness of the developed system had been validated through experimental testing using a three-axis vertical milling machine with a few machining parameters such as cutting speed, depth of cut and tool condition. Overall, the system managed to measure and transfer real-time data from the sensors and transmitted it to the online platform to interface the data.